PROSPECTS FOR THE RAPID DEVELOPMENT OF SECTORS AND REGIONS IN THE ECONOMIC DEVELOPMENT OF THE NEW UZBEKISTAN - Ismoilov Ravshanjon Baxriddinovich; Yusupov Ne’matulla Isoqjanovich; Rapiqov Tohirjon Yuldashbayevich; Boltabayev Dilmurod Abdurashitovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
This article pays special attention to the development of the agro-industrial complex, identifies sources of raw materials for the food, processing industry and public services, and proposes effective ways to expand the stability of Uzbekistan’s export potential in foreign trade processes